A comparative study of pregnancy outcome among women with preeclampsia and normotensive at the Alex Ekwueme Federal University Teaching Hospital Abakaliki, Nigeria - Obi, Chuka N.; Obi, Vitus O.; Nwafor, Johnbosco I.; Onwe, Blessing I.; Onuchukwu, Victor U.; Ugoji, Darlinghton-Peter C.; Ibo, Chukwunenye C. (International Journal of Research in Medical Sciences, 2019)
Background: Preeclampsia is a pregnancy specific multisystem disease and it is associated with increased maternal and perinatal morbidity and mortality. Any factor(s) which could reliably predict the likelihood of serious complications would be very valuable in predicting the associated adverse outcome. Objective of this study compare maternal and fetal outcomes of preeclamptic patients with normotensive control in Alex Ekwueme Federal University Teaching Hospital, Abakaliki, Nigeria. Method: This was a 4-year retrospective case-control study of the pregnancy outcomes among preeclamptic and normotensive women managed in our facility between 1st January 2012 and 31st December 2015. Data analysis was done using Epi Info software 7.2.1. Results: During the study period there were 6,585 deliveries among which 92 of the patients were managed for preeclampsia. This gives a prevalence of 1.4% or 14 per 1000 deliveries. There was no difference in the age and parity of the control. Most of the preeclamptic patients managed over the study period were unbooked for antenatal care in the facility (p value <0.0001). Preeclamptic patients were more likely to be delivered preterm (p value was <0.0001), and by caesarean section compared to the control. They were also more likely to have babies with low birth weights and poorer fetal outcomes. There was no difference in maternal mortality between both groups. Conclusion: Preeclampsia is associated with the unbooked status and poorer perinatal outcome compared with normotensive women. There is need to encourage women to book for antenatal care for prompt identification and management of these women.